Hypermutation in burkholderia cepacia complex is mediated by DNA mismatch repair inactivation and is highly prevalent in cystic fibrosis chronic respiratory infection - Martina, Pablo F (2014)
The Burkholderia cepacia complex (Bcc) represents an important group of pathogens involved in long-term lung infection in cystic fibrosis (CF) patients. A positive selection of hypermutators, linked to antimicrobial resistance development, has been previously reported for Pseudomonas aeruginosa in this chronic infection setting. Hypermutability, however, has not yet been systematically evaluated in Bcc species. A total of 125 well characterized Bcc isolates recovered from 48 CF patients, 10 non-CF patients and 15 environmental samples were analyzed. In order to determine the prevalence of mutators their spontaneous mutation rates to rifampicin resistance were determined. In addition, the genetic basis of the mutator phenotypes was investigated by sequencing the mutS and mutL genes, the main components of the mismatch repair system (MRS). The overall prevalence of hypermutators in the collection analyzed was 13.6%, with highest occurrence (40.7%) among the chronically infected CF patients, belonging mainly to B. cenocepacia, B. multivorans, B. cepacia, and B. contaminans ?the most frequently recovered Bcc species from CF patients worldwide. Thirteen (76.5%) of the hypermutators were defective in mutS and/or mutL. Finally, searching for a possible association between antimicrobial resistance and hypermutability, the resistance-profiles to 17 antimicrobial agents was evaluated. High antimicrobial resistance rates were documented for all the Bcc species recovered from CF patients, but, except for ciprofloxacin, a significant association with hypermutation was not detected. In conclusion, in the present study we demonstrate for the first time that, MRS-deficient Bcc species mutators are highly prevalent and positively selected in CF chronic lung infections. Hypermutation therefore, might be playing a key role in increasing bacterial adaptability to the CF-airway environment, facilitating the persistence of chronic lung infections.